NPRACH-Aware Link Adaptation and Uplink Resource Allocation in NB-IoT Cellular Networks - Yu, Ya-Ju; Wang, Jhih-Kai (IEEE transactions on vehicular technology, 2021)
In narrowband Internet of Things (NB-IoT), a link adaptation technique can be performed, considering multiple resource unit types, repetition numbers, and modulation-coding schemes, to enhance transmission reliability. Then, a base station should allocate downlink and uplink resources for each device using the link adaptation decision to transmit data in NB-IoT frame structures. However, because narrowband physical random access channels (NPRACHs) will occupy the partial uplink radio resource, the uplink transmission of a device using the assigned uplink radio resource without considering NPRACHs will cause severe interference. To solve the above issue, this article investigates the joint link adaptation and uplink resource allocation problem with the consideration of NPRACHs. The objective is to minimize the consumption of radio resources while the uplink data requirement of each device can be satisfied. We prove our target problem is \mathcal {NP} -hard and cannot be approximated with a ratio better than 3/2 . Then, we propose a dynamic-programming algorithm without considering NPRACHs for the link adaptation problem and finally propose an uplink resource allocation algorithm considering NPRACHs based on the dynamic-programming algorithm. We prove that the proposed dynamic-programming algorithm with pseudo-polynomial time can find an optimal solution for the link adaptation problem. Compared with two previous algorithms, the simulation results show the efficacy of the proposed algorithm.